2018
DOI: 10.3389/fpsyt.2018.00312
|View full text |Cite
|
Sign up to set email alerts
|

Cinemotion, a Program of Cognitive Remediation to Improve the Recognition and Expression of Facial Emotions in Schizophrenia: A Pilot Study

Abstract: Objective: Patients with schizophrenia exhibit impaired social cognition, especially in the recognition and expression of facial emotions, aspects of communication profoundly interlinked in an embodied approach of cognition. Nevertheless, many training programs have been developed that focus on either of these deficits but not both. We therefore designed a training program, Cinemotion, intended to remedy the 2 deficits and investigated its feasibility and effects in patients with schizophrenia.Design: Thirty-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 66 publications
(86 reference statements)
0
6
0
Order By: Relevance
“…Social Cognitive Training improved the theory of mind, emotional expression, and recognition and avolition (Bechi et al., 2013; Gaudelus, Virgile, Geliot, The GAIA/Recos Study Team, & Franck, 2016; Gil-Sanz, Fernandez-Modamio, Bengochea-Seco, Arrieta-Rodriguez, & Perez-Fuentes 2013; Palumbo et al, 2017; Sevos et al, 2018; Souto et al, 2018; Taylor et al, 2016) (objective recovery).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Social Cognitive Training improved the theory of mind, emotional expression, and recognition and avolition (Bechi et al., 2013; Gaudelus, Virgile, Geliot, The GAIA/Recos Study Team, & Franck, 2016; Gil-Sanz, Fernandez-Modamio, Bengochea-Seco, Arrieta-Rodriguez, & Perez-Fuentes 2013; Palumbo et al, 2017; Sevos et al, 2018; Souto et al, 2018; Taylor et al, 2016) (objective recovery).…”
Section: Resultsmentioning
confidence: 99%
“…Naeem et al (2015) and Vohs et al (2018) fulfilled the fidelity criteria but included no follow-up; thus, the improvement of Enactment of Treatment Skills was not very clear.Rehabilitation (RCTs): All included RCTs, which contain a rehabilitation program, fulfill the fidelity criteria. The RCTs include only a post-treatment evaluation but not a follow-up evaluation (Table 1) could have a better impact on the improvement of Enactment of Treatment Skills (Bechi et al, 2013; Bio & Gattaz, 2011; Byrne et al, 2013; Choi et al, 2018; Garrido et al, 2013; Gaudelus et al, 2016; Gharaeipour & Scott, 2012; Gil-Sanz et al, 2013; Gomar et al, 2015; Iwata et al, 2017; Kurtz et al, 2015; Ojeda et al, 2012; Palumbo et al, 2017; Pena et al., 2016; Rocha & Queiros, 2013; Sanchez et al, 2014; Sevos et al, 2018; Souto et al, 2018; Taylor et al, 2016; Thomas et al, 2018; Veltro et al, 2011). Case studies (CBT, MCT, MCTR, MERIT, and Rehabilitation): Balzan and Galletly (2015), Peyroux and Franck (2016), and Grant et al (2014) followed the fidelity criteria thoroughly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of studies, researchers have employed the well‐known Facial Action Coding System (FACS) to convert the action units’ descriptive scores into seven emotions, including “surprised,” “contemptuous,” “fearful,” “happy,” “angry,” “sad,” and “disgusted” (Martinez et al., 2019). A previous study has demonstrated that SCZ patients often exhibit uncertainty in facial expressions compared to healthy controls (Sevos et al., 2018). Moreover, it has been reported that SCZ patients exhibit incongruent facial expressions and are significantly worse than healthy controls in their responses to emotional stimuli and during social interactions (Bersani et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…"angry," "sad," and "disgusted" (Martinez et al, 2019). A previous study has demonstrated that SCZ patients often exhibit uncertainty in facial expressions compared to healthy controls (Sevos et al, 2018).…”
Section: Introductionmentioning
confidence: 99%